Fracture Characterization of Asphalt Mixtures with High Recycled Content Using Illinois Semicircular Bending Test Method and Flexibility Index. Issue 1 (2016) - Ozer, Hasan; Al-Qadi, Imad L.; Singhvi, Punit; Khan, Tamim; Rivera-Perez, Jose; El-Khatib, Ahmad
Using reclaimed and recycled materials in asphalt mixtures is one of the most commonly used sustainable strategies, which results in cost savings and environmental benefits because they replace virgin materials. Commonly used recycled, reclaimed asphalt pavement (RAP) and recycled asphalt shingles (RAS) can pose challenges because their inclusion in the asphalt mixture may adversely affect pavement performance. This paper presents the recently developed fracture testing method, the Illinois semicircular bending (IL-SCB) fracture geometry at 25°C with a displacement rate of 50 mm/min. The flexibility index (FI), derived from the IL-SCB test results, was introduced to rank the potential cracking resistance of mixes. The developed testing protocol provides a practical and reliable approach to screen the capacity of mixes to resist cracking. An application of the IL-SCB test method and FI is presented using laboratory-prepared and compacted mixes with varying proportions of RAP and RAS. The mixes were designed and prepared with strict volumetric requirements, enabling comparison of the effects of RAP and RAS only. Fracture testing was conducted at low and intermediate temperatures. Fracture testing results indicate a consistent trend at intermediate temperatures using both fracture energy and the FI. The discrimination potential and sensitivity of the FI to even small changes in the mix design properties enable integration of the IL-SCB test method and FI as a performance quality indicator. Finally, the FI and Hamburg wheel-tracking test results are combined in an interaction plot that can be used as a performance-based mix design tool along with volumetrics requirements.